Effect of Family Characteristics on Stunting Events in Toddlers Aged 6-59 Months: Analisis Sebaran dan Determinan Stunting berdasarkan Karakteristik Keluarga pada Balita Usia 6 – 59 Bulan - Izah, Nilatul; Zulfiana, Evi; Rahmanindar, Nora (Universitas Muhammadiyah Sidoarjo, 2020)
Stunting is defined as a chronic condition that is a picture of stunted growth due to lack of nutrition in the long run and or due to other problems. Stunting, especially in infants, can slow down both physical and mental development of children, so special attention is needed. Many factors influence the incidence of stunting, including family characteristics such as family economic status, mother's education, parents 'height and parents' level of knowledge about toddler nutrition. The purpose of this study is to analyze the distribution and determinant of stunting based on family characteristics in toddlers aged 6-59 months. This type of research is quantitative with casecontrol design. The research sample was taken by consecutive sampling. The sample used in this study is the case and control group selected by case and control ratio of 1: 1. The case group consisted of mothers of toddlers aged 6 - 59 months who experienced stunting and the control group consisted of mothers of toddlers aged 6 - 59 months who did not experience stunting (normal). The results showed that maternal age affected stunting, mother's education did not affect stunting, mother's work did not affect stunting, mother's knowledge affected stunting, parental height affected stunting.